Prevalence of osteoarthritis knee: four year study based on digital records of comprehensive healthcare setup at Mumbai, India - Bhandarkar, Prashant; Priti, Patil; Chander, Shekhar; Nandan, Kamat (International Journal Of Community Medicine And Public Health, 2017)
Background: Ageing starts with chronic diseases, which affects quality of life, osteoarthritis of knee (OAK) is one of major disease, affecting significant geriatric population. Females reported significantly more prevalent than males. Diagnosed cases are treated with exercise, physiotherapy and some medication however in extreme cases knee arthroplasty surgeries are performed. Study aims to examine prevalence of OAK, its association with respect to age group, sex and working status. It also aims, to examine the total knee arthroplasty (TKA) surgery incidences in community during study period. Methods:Digital data from January 2011 to December 2014 gathered in hospital information system was analyzed. Potential cases of OAK were estimated using ‘keyword’ search program. Yearly prevalent population of OAK was estimated and their associations calculated for age-group, sex and work status. Logistic regression analysis was performed. Patients undergone through TKA surgery were traced and yearly incidence was examined. Results: On an average 3.62 per hundred yearly prevalence was found, it increased from 3.31 (2011) to 3.91 (2014). Females were 63%, whereas males were 37%. Among overall prevalent cases, 4.23% were undergone TKA surgeries. Compared to males, odd for females was found at high risk (1.393). Compared to retired population, odd for housewife was found at high risk (1.269). Conclusions:Study documents four years, prevalence rate of OAK and surgery incidences. In study population females shared better chance of surgical intervention along with males. Policy intervention to manage costly musculoskeletal surgeries are needed with preventive public health awareness programs.